The Relationship between Successful Completion and Sequential Movement in Self-Paced Distance Courses - Lim, Janine M. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2016)
A course design question for self-paced courses includes whether or not technological measures should be used in course design to force students to follow the sequence intended by the course author. This study examined learner behavior to understand whether the sequence of student assignment submissions in a self-paced distance course is related to successful completion of the course. The study included 543 students in 89 different general education courses at a private university in the United States during a two year period. Results indicate that students who completed at least one assignment or exam out of the intended sequence of instruction were more likely to complete the course. Results were consistent when replicating the analysis with subsets of the data by course characteristics such delivery type, content, course format, and course level; and student demographics such as ethnicity, gender, GPA, and class standing. Learner control and self-direction within online self-paced courses should be included in course design to increase the likelihood of learner successful completion. Additional research could benefit course design and student support to promote higher rates of completion in self-paced courses.